Inflammasomes: novel therapeutic targets for metabolic syndrome? - Cao, Pengyu; Yang, Yulin; Zhang, Ningning; Wang, Bojian; Gong, Zhenwei (Frontiers in Endocrinology, 2025)
Chronic inflammation is a hallmark for Metabolic Syndrome (MetS). It is also one of the most important risk factors for insulin resistance and metabolic disorders. Inflammasomes, which are intracellular multiprotein complexes within the innate immune system, regulate the production and maturation of pro-inflammatory cytokines including interleukin-1β (IL-1β) and IL-18 upon sensing pathogens or danger signals in the cytosol. A growing body of evidence indicates that inflammasomes play a pivotal role in the pathophysiology and progression of metabolic diseases, as deficiency in the key component of inflammasomes protects mice from high fat diet induced obesity and insulin resistance. Thus, in this review, we will summarize the role of inflammasomes in MetS and how to treat MetS by targeting inflammasomes. This may provide novel insights and therapeutic targets for treating metabolic disorders.